Fluid and fuel intake during exercise - Coyle, E. F. (Journal of Sports Sciences, 2004)
The amounts of water, carbohydrate and salt that athletes are advised to ingest during exercise are based upon their effectiveness in attenuating both fatigue as well as illness due to hyperthermia, dehydration or hyperhydration. When possible, fluid should be ingested at rates that most closely match sweating rate. When that is not possible or practical or sufficiently ergogenic, some athletes might tolerate body water losses amounting to 2% of body weight without significant risk to physical well-being or performance when the environment is cold (e.g. 5-10 degrees C) or temperate (e.g. 21-22 degrees C). However, when exercising in a hot environment ( > 30 degrees C), dehydration by 2% of body weight impairs absolute power production and predisposes individuals to heat injury. Fluid should not be ingested at rates in excess of sweating rate and thus body water and weight should not increase during exercise. Fatigue can be reduced by adding carbohydrate to the fluids consumed so that 30-60 g of rapidly absorbed carbohydrate are ingested throughout each hour of an athletic event. Furthermore, sodium should be included in fluids consumed during exercise lasting longer than 2 h or by individuals during any event that stimulates heavy sodium loss (more than 3-4 g of sodium). Athletes do not benefit by ingesting glycerol, amino acids or alleged precursors of neurotransmitter. Ingestion of other substances during exercise, with the possible exception of caffeine, is discouraged. Athletes will benefit the most by tailoring their individual needs for water, carbohydrate and salt to the specific challenges of their sport, especially considering the environment's impact on sweating and heat stress.